2001
DOI: 10.1128/jvi.75.12.5504-5517.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vif Is Largely Absent from Human Immunodeficiency Virus Type 1 Mature Virions and Associates Mainly with Viral Particles Containing Unprocessed Gag

Abstract: Vif is a human immunodeficiency virus type 1 (HIV-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 73 publications
(56 reference statements)
3
19
0
Order By: Relevance
“…Affinity for RNA molecules is consistent with the observations that APOBEC3G is incorporated into unrelated retroviruses (21,37,38). Since Vif and APOBEC3G are likely to be present at the site of virus assembly, removal of APOBEC3G by Vif-induced polyubiq- (2,4,9,12,28,30,34,58). The proteasome inhibitor experiments presented here indicated that the majority of HIV-1 Vif molecules which were competent for packaging were removed during virus assembly by the proteasome pathway (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Affinity for RNA molecules is consistent with the observations that APOBEC3G is incorporated into unrelated retroviruses (21,37,38). Since Vif and APOBEC3G are likely to be present at the site of virus assembly, removal of APOBEC3G by Vif-induced polyubiq- (2,4,9,12,28,30,34,58). The proteasome inhibitor experiments presented here indicated that the majority of HIV-1 Vif molecules which were competent for packaging were removed during virus assembly by the proteasome pathway (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…The packaging efficiency of Vif is therefore comparable to that of Env (58). In addition, the results from our study offer a possible explanation for the apparent paucity of virus-associated Vif reported in previous studies (14,54), which could be accounted for by the gradual processing of full-length virus-associated Vif into a short C-terminal fragment (p7‫,)ء‬ carrying the major antigenic epitope, and a longer N-terminal fragment that is generally not or only very inefficiently recognized by available polyclonal antibodies or MAbs (not shown). Thus, our results suggest that packaging of Vif occurs at levels that match or exceed those of reverse transcriptase or integrase, supporting the notion that packaging of Vif might be functionally relevant.…”
Section: Discussionsupporting
confidence: 68%
“…3) (6,11,22,38,39,42,61,64), even after removal of contaminating vesicles and extravirion proteins by subtilisin treatment. Although a consensus that Vif is associated with viral cores is generally emerging (11,39,42), the functional relevance of Vif packaging remains unresolved.…”
Section: Vol 77 2003mentioning
confidence: 99%